2021
DOI: 10.3390/educsci11010031
|View full text |Cite
|
Sign up to set email alerts
|

Student Burnout: A Case Study about a Portuguese Public University

Abstract: Burnout is increasingly present in organizations and in the most diverse professions, namely, in university students. Burnout can have negative repercussions on their well-being and can even lead them to abandon their studies. The objective of the study focuses on academic burnout and taking medication as a consequence of the requirements of the academic path of students at a Portuguese public university. To achieve this goal, a quantitative methodology was used, consisting of the distribution of a questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 55 publications
3
25
0
6
Order By: Relevance
“…Next, the present study did not register a difference in PsyCap due to household income. Similarly, a Portuguese study found household income does not correlate with burnout levels among university students . Nevertheless, an engineering study urged financial aid or differential tuition fees to be offered to underprivileged students .…”
Section: Discussionmentioning
confidence: 99%
“…Next, the present study did not register a difference in PsyCap due to household income. Similarly, a Portuguese study found household income does not correlate with burnout levels among university students . Nevertheless, an engineering study urged financial aid or differential tuition fees to be offered to underprivileged students .…”
Section: Discussionmentioning
confidence: 99%
“…A feeling of being incompetent can further reduce the motivation to study leading to a performance deterioration [11] with increased perceived stress [12]. This vicious cycle can result in burnout and prompt students to abandon their studies [13].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the study conducted by (Salgado & Au-Yong-oliveira, 2021) explained that saturation has a very big impact on the time of Distance learning. This can be seen from the study results, which explain the negative effects of burnout on well-being and can even cause them to abandon their studies.…”
Section: Introductionmentioning
confidence: 99%